Epiblast cells gather onto the anterior mesendoderm and initiate brain development without the direct involvement of the node in avian embryos: Insights from broad-field live imaging - Yoshihi, Koya; Iida, Hideaki; Teramoto, Machiko; Ishii, Yasuo; Kato, Kagayaki; Kondoh, Hisato (Frontiers in Cell and Developmental Biology, 2022)
Live imaging of migrating and interacting cells in developing embryos has opened a new means for deciphering fundamental principles in morphogenesis and patterning, which was not possible with classic approaches of experimental embryology. In our recent study, we devised a new genetic tool to sparsely label cells with a green-fluorescent protein in the broad field of chicken embryos, enabling the analysis of cell migration during the early stages of brain development. Trajectory analysis indicated that anterior epiblast cells from a broad area gather to the head axis to form the brain primordia or brain-abutting head ectoderm. Grafting the mCherry-labeled stage (st.) 4 node in an anterior embryonic region resulted in the anterior extension of the anterior mesendoderm (AME), the precursor for the prechordal plate and anterior notochord, from the node graft at st. 5. Grafting the st. 4 node or st. 5 AME at various epiblast positions that otherwise develop into the head ectoderm caused local cell gathering to the graft-derived AME.Grafting the mCherry-labeled stage (st.) 4 node that extends the anterior mesendoderm (AME) into the host embryo or st. 5 AME at various anterior epiblast positions that otherwise develop into the head ectoderm caused local cell gathering to the graft-derived AME. The node was not directly associated with this local epiblast-gathering activity. The gathered anterior epiblast cells developed into secondary brain tissue consisting of consecutive brain portions, e.g., forebrain and midbrain or midbrain and hindbrain, reflecting the brain portion specificities inherent to the epiblast cells. The observations indicated the bipotentiality of all anterior epiblast cells to develop into the brain or head ectoderm. Thus, a new epiblast brain field map is proposed, allowing the reinterpretation of classical node graft data, and the role of the AME is highlighted. The new model leads to the conclusion that the node does not directly participate in brain development.